P367 Nutrition advice for IBD patients as a useful complementary strategy: a single-centre cohort intervention. (25th January 2019) - Fortuna, M; Di Ruscio, M; Variola, A; Massella, A; Geccherle, A
Abstract: Background: Diet plays an important role in patients with inflammatory bowel disease (IBD) since it may influence intestinal inflammation, through an alteration of gut microbiome, and affecting gastrointestinal permeability. Nutrition problems may have a strong effect on patient health, nutritional status and quality of life. However, scientific studies lack solid evidence to support specific dietary recommendations and this is reflected in conflicting dietary beliefs in clinical practice. In our Multispecialistic Centre for Recto-Intestinal Diseases (IBD Unit) at Negrar Hospital, we give a nutrition consultation to provide tailored dietary advice to all IBD patients. The aim of this investigation was to assess the efficacy of our nutritional intervention on disease symptoms and patients quality of life (QoL). Methods: From October 2017 to April 2018, we evaluated patients with ulcerative colitis (UC) in clinical remission (according to Partial Mayo Score (PMS) for UC: remission score (rs) < 2) and gave them dietary suggestions, including antioxidant, vitamin, probiotic supplementation and nutritional deficiency screening. Dietary counselling was based on: elimination of dairy products if lactose intolerance was detected, intake limitation of refined sugars, alcohol, gluten-based grains, meat and saturated fats, intake promotion of high-fibre (legumes, vegetable, whole grains), fermented, n-3 rich foods (fish, dried fruit), aliments with antioxidant activity (olive oil, green tea, turmeric, red fruit), and vitamin D supplementation. After dietary advice these patients were reassessed after 1 month, 3 months and 6 months. We also recruited a control group of UC patients, homogeneous in disease activity, current therapy (tp), age, sex and disease extent. Results: We enrolled 32 UC patients in clinical remission, whom underwent nutritional evaluation, 17 had PMS: 0, 15 PMS: 1 [21 female, mean age 38 years old, 16 left-sided colitis, 9 proctitis, 7 pancolitis, 21 patients treated with mesalazine, 7 azathioprine, 4 biologic tp (3 adalimumab, 1 Infliximab)]. After 6 months, all patients receiving nutrition advice, considered diet to be a very important tool to relieve disease symptoms. Self-reported QoL was improved than control group. PMS was stable or reduced to 0, in comparison to control group, where we could observe mild flares in 9 patients. No nutrition treatment-related adverse events nor vitamin and trace elements deficiency were observed. Conclusions: Our investigation on nutritional support in IBD shows that diet is important and effective as a complementary tp, in UC patients in remission. High-quality dietary intervention studies are needed to have a better understanding of dietary practices in improving symptoms and to create strong evidence-based dietary guidelines for IBD patients.